Effects of alkalization therapy on hepatocellular carcinoma: a retrospective study - Isowa, Masahide; Hamaguchi, Reo; Narui, Ryoko; Morikawa, Hiromasa; Wada, Hiromi (Frontiers in Oncology, 2023)
Background: In hepatocellular carcinoma (HCC) patients, is difficult to prevent recurrence even when remission is achieved. In addition, even with the advent of drugs that are effective for the treatment of HCC, a satisfactory extension of patient survival has not been achieved. To overcome this situation, we hypothesized that the combination of alkalization therapy with standard treatments will improve the prognosis of HCC. We here report the clinical results of HCC patients treated with alkalization therapy at our clinic. Patients and methods: Patients with HCC treated at Karasuma Wada Clinic (in Kyoto, Japan), from January 1, 2013, to December 31, 2020 were analyzed. Overall survival (OS) from both the time of diagnosis and the start of alkalization therapy for each patient was compared. The mean urine pH was also calculated as a surrogate marker of tumor microenvironment pH, and OS from the start of alkalization therapy was compared between patients with a mean urine pH of  7.0 and those with a mean urine pH of < 7.0. Results: Twenty-three men and six women were included in the analysis, with a mean age at diagnosis of 64.1 years (range: 37–87 years). Seven of the 29 patients had extrahepatic metastases. Patients were divided into two groups according to their mean urine pH after the initiation of alkalization therapy: 12 of the 29 patients had a mean urine pH of  7.0, and 17 had a mean urine pH of < 7.0. The median OS from diagnosis was 95.6 months (95% confidence interval [CI] = 24.7-not reached), and from the start of alkalization therapy was 42.3 months (95% CI = 8.93-not reached). The median OS from the start of alkalization therapy in patients with a urine pH of  7.0 was not reached (n = 12, 95%CI = 3.0-not reached), which was significantly longer than that in patients with a pH of < 7.0 (15.4 months, n = 17, 95%CI = 5.8-not reached, p < 0.05). Conclusions: The addition of alkalization therapy to standard therapies may be associated with more favorable outcomes in HCC patients with increased urine pH after alkalization therapy.